1998
DOI: 10.1177/107769909807500410
|View full text |Cite
|
Sign up to set email alerts
|

Women Making News: Gender as a Variable in Source Selection and Use

Abstract: An important dimension ofagenda setting is the way in which the media frame the issues and events they present to the public. This article focuses on one of the most important dimensions offraming: choice of information source-the selections journalists make from among the many possible and potential holders of information of those sources whose information and viewpoints will actually be included in the news. In particular, this content analysis of ten years of three southern newspapers focuses on the inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
3
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 2 publications
(2 reference statements)
4
101
3
12
Order By: Relevance
“…Previous research in other national contexts has repeatedly found that men are more likely than women to be used as expert sources in newspapers (Armstrong and Nelson 2006;Zoch and VanSlyke Turk 1998) and on television, particularly for stories involving "hard news" topics such as politics (Cann and Mohr 2001;Desmond and Danilewicz 2010). When women do appear as sources on television news, it tends to be in connection with "softer" topics, such as health or lifestyle, and they often are represented in a "ritualized" way, offering a "contained and safe" representation of how actions taken in the public sphere affect those in the private sphere (Rakow and Kranich 1991, 16).…”
Section: Literature: News Sourcesmentioning
confidence: 99%
“…Previous research in other national contexts has repeatedly found that men are more likely than women to be used as expert sources in newspapers (Armstrong and Nelson 2006;Zoch and VanSlyke Turk 1998) and on television, particularly for stories involving "hard news" topics such as politics (Cann and Mohr 2001;Desmond and Danilewicz 2010). When women do appear as sources on television news, it tends to be in connection with "softer" topics, such as health or lifestyle, and they often are represented in a "ritualized" way, offering a "contained and safe" representation of how actions taken in the public sphere affect those in the private sphere (Rakow and Kranich 1991, 16).…”
Section: Literature: News Sourcesmentioning
confidence: 99%
“…Women are consistently underrepresented in the news media while males continue to dominate (American Press Institute, 2002;Cann and Mohr, 2001;Zoch and Turk, 1998). Schell and Rodriguez (2000) noted that since males dominate the media, opportunities for females are repressed.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, 15 dichotomous nominal variables (present vs. not present) were established for classifying sources into types, based on a list of source types extrapolated from similar studies (Albaek, Christiansen, & Togeby, 2003;Armstrong, 2004;Barr, Irlbeck, & Akers, 2012;Gasher, Hayes, Hackett, Gutstein, Ross, & Dunn, 2007;Sumpter & Braddock, 2002;Sumpter & Lukaszewski, 2001;Telg & Raulerson, 1999;Zoch & Turk, 1998). Dichotomous measurement of independent variables has been found to have little serious effect on the probability statements underlying parametric procedures of inferential statistics, that is, common inferential statistical procedures, for example, ANOVA, may be used on such data (Field, 2009).…”
Section: Researchmentioning
confidence: 99%